Epidemiology and clinical features of imported malaria: a 14-year retrospective single-centre descriptive study in Prague, Czech Republic - Milan Trojánek; Vyacheslav Grebenyuk; Lenka Richterová; Ivana Zicklerová; Eva Nohýnková; Zdenka Manďáková; Jakub Kantor; Hana Roháčová; František Stejskal (Malaria Journal, 2022)
Abstract Background Malaria represents one of the most important imported tropical infectious diseases in European travellers. The objective of the study was to identify changes in the epidemiological features of imported malaria and to analyse the clinical findings and outcomes of imported malaria. Methods This single-centre descriptive study retrospectively analysed the medical records of all imported malaria cases in travellers treated at the Department of Infectious Diseases of University Hospital Bulovka in Prague from 2006 to 2019. Results The study included 203 patients with a median age of 37 years (IQR 30–48) and a male to female ratio of 3.72:1. Plasmodium falciparum was the predominant species (149/203), and its proportion significantly increased from 35/60 cases (58.3%) in 2006–2011 to 69/80 (86.3%) in 2016–2019 (p < 0.001). In contrast, the incidence of Plasmodium vivax malaria decreased from 19/60 cases (31.7%) in 2006–2011 to 5/80 (6.3%) in 2016–2019 (p < 0.001). Malaria was imported from sub-Saharan Africa in 161/203 cases (79.3%). The proportion of travellers from Southeast and South Asia decreased from 16/60 (26.7%) and 6/60 (10.0%) in 2006–2011 to 2/80 (2.5%) and no cases (0.0%) in 2016–2019, respectively (p < 0.001 and p = 0.006). Tourism was the most common reason for travel (82/203), however, the proportion of non-tourists significantly increased over time from 29/60 (48.3%) in 2006–2011 to 55/80 (68.8%) in 2016–2019, p = 0.015. Severe malaria developed in 32/203 (15.8%) patients who were significantly older (p = 0.013) and whose treatment was delayed (p < 0.001). Two lethal outcomes were observed during the study period. Conclusions This study demonstrated a significant increase in P. falciparum malaria, which frequently resulted in severe disease, especially in older patients and those with delayed treatment initiation. The rising proportion of imported malaria in non-tourists, including business travellers and those visiting friends and relatives, is another characteristic finding analogous to the trends observed in Western European and North American centres. The described changes in the aetiology and epidemiology of imported malaria may serve to optimize pre-travel consultation practices and improve post-travel diagnostics and medical care.